2014 IEEE International Conference on Communications (ICC) 2014
DOI: 10.1109/icc.2014.6883685
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of long-distance Wi-Fi connections: An empirical study

Abstract: Long-distance Wi-Fi technology has shown promise in several network applications that cannot utilize conventional technologies effectively. Although the network performance of WiFi technology is affected by a number of environmental factors, there is a dearth of long-term, continuous, and systematic studies on the correlations between those factors and the technology's performance. In this study, we deployed a long-distance Wi-Fi testbed on our campus and conducted a one-year experiment. Comprehensive data ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…After all, the propagation of electromagnetic waves in the space medium would change with changes in climatic factors. For instance, the rain attenuation of electromagnetic waves was attributed to the RF absorption and attenuation by the raindrops in the atmosphere, which ultimately affected the communication performance [24].…”
Section: Plos Onementioning
confidence: 99%
“…After all, the propagation of electromagnetic waves in the space medium would change with changes in climatic factors. For instance, the rain attenuation of electromagnetic waves was attributed to the RF absorption and attenuation by the raindrops in the atmosphere, which ultimately affected the communication performance [24].…”
Section: Plos Onementioning
confidence: 99%
“…Analysing how the weather impacts on outdoor wireless networks can be carried out from experimental data obtained by an accurate setup [6]. Once performance data and weather data are gathered by minute, they can be statically analysed in order to find precise correlations [7]. It has been shown that both groups of data (meteorological and wireless link quality) are significantly correlated [8], but this type of statistical analysis presents some limitations.…”
mentioning
confidence: 99%